(3JHjjf GdCQGFc aj EQSGd GdfHi Edi GdedGFcs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3eSCdI eG jbhdhf ai bhd GdYdeGA QVi Gddg Yfge Gfg Udi dGdg Ydjg hSde de jHYK Edi GdedGFcI s
(3BNQgG (B:s
(3hgPg GdbGYOI cGdeLeY YdjgG , heef fU YdjgG GdTGaYi QVi Gddg Yfg , hGdMeO ddg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3HChdgG Jedc SfI (B1201(3g` Ydi ghGeTgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJhMjO hGdedd hGdfMds